Vitamin D ameliorates prediabetic cardiac injure via modulation of the ErbB4/ferroptosis signaling axis - Miao, Yufan; Zhang, Yujing; Zhang, Luoya; Chen, Hao; Tang, Lulu; Li, Wenjie; Gu, Chenxi; Lang, Lili; Li, Xing; Song, Hanlu (Frontiers in Immunology, 2025)
Vitamin D (VD) deficiency is closely associated with metabolic health and cardiac function in prediabetic patients, yet its underlying mechanisms remain unclear. This study investigated the role of VD intervention in prediabetic cardiac injury through in vivo and in vitro models, with particular focus on the ErbB4/ferroptosis axis. Using a high-fat diet-induced KKAy prediabetic mouse model, we observed significant metabolic abnormalities (increased body weight, hyperglycemia, insulin resistance) and cardiac remodeling (cardiac hypertrophy and functional impairment) (P<0.05). Remarkably, 16-week vitamin D (VD3) supplementation substantially ameliorated these pathological changes and reduced serum cardiac injury markers (P<0.05). Mechanistic studies revealed that VD3 downregulated myocardial NRG1 expression, inhibited ErbB4 phosphorylation (p-ErbB4) and YAP activation (p-YAP), while reversing the abnormal expression of ferroptosis-related proteins. In vitro experiments confirmed that high glucose combined with palmitic acid (HGPA) induced ferroptosis in H9c2 cardiomyocytes, which was alleviated by 1,25(OH)2D3 intervention through suppression of ErbB4 phosphorylation. Notably, combined treatment with 1,25(OH)2D3 and the ErbB4 phosphorylation inhibitor dacomitinib demonstrated synergistic protective effects. Our findings not only expand the understanding of the association between prediabetes and VD, but also reveal a relationship between ErbB4 and cardiac ferroptosis in prediabetic conditions.